Hubungan Hipertensi dengan Kejadian Sindrom Koroner Akut: Studi Kasus–Kontrol - MADE BAGUS MANIK SATRIA MAHOTTAMA; KADEK SURYA ATMAJA; SRI MASYENI; SAKTIVI HARKITASARI; ADITYA YUDISTIRA (Hang Tuah Medical Journal, 2026)
Abstract Background: Acute Coronary Syndrome (ACS) is a major cardiovascular emergency associated with substantial morbidity and mortality. Hypertension is considered an important risk factor, yet local evidence remains essential. Objective: evaluate the relationship between hypertension and ACS occurrence in two referral hospitals in Bali, Indonesia. Methods: A hospital-based case–control study using medical record data was conducted at Karangasem and Tabanan District Hospitals. A total of 176 subjects were included: 88 ACS cases and 88 non-ACS controls. Purposive sampling with age- and sex-matching was applied. Bivariate analysis employed Chi-square test, reporting OR with 95% CI. Results: Most participants were aged >45 years (96.6%) and male (65.9%). Among cases, the most frequent ACS subtype was unstable angina (43.2%), followed by NSTEMI (34.1%) and STEMI (22.7%). The most common presenting symptoms were dyspnea (84.1%) and typical chest pain (79.5%). Hypertension was present in 39.8% of cases and 18.2% of controls. Hypertension was significantly related to ACS (p=0.002 OR of 2.97; 95% CI: 1.491–5.923).Conclusion: Hypertension is significantly related to ACS occurrence and increases the odds of ACS by nearly threefold.